Xamarin cross-platform mobile application development : master the skills required to develop cross-platform applications from drawing board to app store(s) using Xamarin : a course in three modules. (Learning path., 2016)
Master the skills required to develop cross-platform applications from drawing board to app store(s) using Xamarin About This Book Learn to deliver high-performance native apps that leverage platform specific acceleration, complied for native performance Learn development techniques that will allow you to use and create custom layouts for cross-platform UI Gain the knowledge needed to become more efficient in testing, deploying, and monitoring your applications Implement application life cycle management concepts to manage cross-platform projects Who This Book Is For Mobile application developers wanting to develop skills required to steer cross-platform applications using Xamarin. What You Will Learn Share C# code across platforms and call native Objective-C or Java libraries from C# Submit your app to the Apple App Store and Google Play Use the out-of-the-box services to support third-party libraries Find out how to get feedback while your application is used by your users Create shared data access using a local SQLite database and a REST service Test and monitor your applications Gain memory management skills to avoid memory leaks and premature code cycles while decreasing the memory print of your applications Integrate network resources with cross-platform applications Design and implement eye-catching and reusable UI components without compromising on nativity in mobile applications In Detail Developing a mobile application for just one platform is becoming a thing of the past. Companies expect their apps to be supported on iOS, Android and Windows Phone, while leveraging the best native features on all three platforms. Xamarin's tools help ease this problem by giving developers a single toolset to target all three platforms. The main goal of this course is to equip you with knowledge to successfully analyze, develop, and manage Xamarin cross-platform projects using the most efficient, robust, and scalable implementation patterns. Module 1 is a step-by-step guide to building real-world applications for iOS and Android. The module walks you through building a chat application, complete with a backend web service and native features such as GPS location, camera, and push notifications. Additionally, you'll learn how to use external libraries with Xamarin and Xamarin. Forms. Module 2 provide you recipes on how to create an architecture that will be maintainable, extendable, use Xamarin. Forms plugins to boost productivity. We start with a simp ...